mGluR5 Mediates Dihydrotestosterone-Induced Nucleus Accumbens Structural Plasticity, but Not Conditioned Reward - Gross, Kellie S.; Moore, Kelsey M.; Meisel, Robert L.; Mermelstein, Paul G. (Frontiers in Neuroscience, 2018)
Gonadal hormones play a vital role in driving motivated behavior. They not only modulate responses to naturally rewarding stimuli, but also influence responses to drugs of abuse. A commonality between gonadal hormones and drugs of abuse is that they both impact the neurocircuitry of reward, including the regulation of structural plasticity in the nucleus accumbens (NAc). Previous hormonal studies have focused on the mechanisms and behavioral correlates of estradiol-induced dendritic spine changes in the female NAc. Here we sought to determine the effects of androgens on medium spiny neuron (MSN) spine plasticity in the male NAc. Following treatment with the androgen receptor agonist dihydrotestosterone (DHT), MSNs in castrated male rats exhibited a significant decrease in dendritic spine density. This effect was isolated to the shell subregion of the NAc. The effect of DHT was dependent on mGluR5 activity, and local mGluR5 activation and subsequent endocannabinoid signaling produce an analogous NAc shell spine decrease. Somewhat surprisingly, DHT-induced conditioned place preference remained intact following systemic inhibition of mGluR5. These findings indicate that androgens can utilize mGluR signaling, similar to estrogens, to mediate changes in NAc dendritic structure. In addition, there are notable differences in the direction of spine changes, and site specificity of estrogen and androgen action, suggesting sex differences in the hormonal regulation of motivated behaviors.